In-vitro Inhibition of Mineralisation of Urinary Stone Forming by Some Dry-fruit Extracts - Rao, T.V.R.K.; Bano, Sofia (Asian Journal of Chemistry, 2010)
Water extracts of some dry fruits, viz., raisins, dried dates, currants or cashew have been studied as inhibitors in the mineralisation of urinary stone forming minerals, viz., calcium phosphate, oxalate or carbonate. Inhibition efficiency has been studied in different experimental models. Utility of these dry fruits in urolithiasis inhibition has been discussed.